Konseling Gizi Ibu Hamil Anemia Untuk Meningkatkan Status Kesehatan Maternal Di Praktek Bidan Mandiri - Diana Putri (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Anemia in pregnancy is still a major problem experienced by almost half of pregnant women in all countries in the world including Indonesia. Many pregnant women refuse and do not comply with taking FE tablets for various reasons so that the prevalence of anemia in pregnant women is still high. A mother is said to be compliant with taking FE tablets if ≥ 90 % of the amount should have been taken. Anemia in pregnancy is a national problem because it reflects the value of the socio-economic welfare of the community, and has a very large impact on the quality of human resources, which is called "potential danger to mother and child". The purpose of the service is to provide education on the addition of nutrients to reduce anemia. Based on the results of the activity, the delivery of material. The results of this activity are the participation of pregnant women during educational and simulation activities running smoothly, indicated by the activeness of pregnant women and attended by all pregnant women class participants and there is an increase in understanding of anemia by 50 %. The service was carried out on 23 June 2023 at Waonosari Polindes in the class of pregnant women. The method used was education and simulation in making soy milk and date pudding. Indonesia itself has an anemia prevention program for pregnant women by providing a minimum FE supplement of 90 tablets during pregnancy.